Sosialisasi Pemasaran Digital Dengan Cara Membangun Brand bagi Cafe StoenHouse di Desa Lebak Muncang - Octavia, Dila; Nurlatifah, Eva Nurlatifah (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2022)
Micro, small and medium enterprises (MSMEs) are one of the important instruments in economic development in Lebak Muncang Village. MSMEs located in Lebak Muncang Village have enormous potential for success, but in their development they still have limited understanding and use of digital technology. In this service activity the method used is Participation Action Research, the author helps one of the MSMEs, namely Stoenhouse, in attracting new customers using digital media and helps provide sales education for its processed product, namely StoenMeal. This model was obtained after carrying out social reflection activities and participatory planning programs which were then carried out with the implementation of predetermined activities. The success of this service activity can be seen from the response provided by Stoenhouse. The conclusion of this service activity is the socialization of digital marketing by building branding for the StoenHouse cafe in Lebak Muncang Village